A DEVELOPMENT OF AREA RAINFALL INDEX FOR FLOOD PROBABILITY ANALYSIS IN WATERSHEDS - Azizah, Siti
This study concerns with the determination of empirical rainfall threshold values that can differentiate flood events in watersheds and catchment areas in Indonesia. First, an index that represents watershed area rainfall was developed from near real-time Global Satellite Mapping of Precipitation (GSMaP-NRT) data. The index is defined as a multiplicative product of two indices that respectively represent antecedent rainfall, defined as aggregate rainfall over a period comparable to the time of concentration, and actual (24-hour) rainfall observed on the date of flood events. The resulted single index, referred to as Flood Triggering Rainfall Index (FTRI), was than compared with observed flood frequency and magnitude to determine a threshold based on the empirical cumulative distribution function. It is found that for a relatively large watershed the threshold value correspond to the 10th percentile (FTRI10), while the 25th percentile (FTRI25) is more suitable for smaller watershed. In addition, extreme flood events were identified at higher thresholds corresponding to FTRI90. These thresholds have been evaluated by calculating the sensitivity, specificity, and efficiency metrics for some watersheds and catchment areas. Although the number of cases is still limited, results of the evaluation indicate that the rainfall thresholds defined by FTRI are potentially useful for analysing probability of flood events.